Functional Recovery & Neurogenesis after Transplantation of Stem Cells from Human Umbilical Cord Blood into Spinal Cord Injured Rats - Endegena Gemta (Egyptian Spine Association, 2013)
Background Data: Transplantation of umbilical cord blood stem cells into damaged spinal cords was used experimentally for several years. Such transplants survive and integrate to some degree with the host tissue and may be associated with functional improvement. Purpose: To find out the functional improvement, and axon regeneration in spinal cord injured rats after human umbilical cord blood stem cells (HUCBs) transplantation. Study Design: Prospective analytic animal experimental study. Material and Methods: Forty rats were recruited and divided into four groups, each containing 10 rats: Group (1): Control group with no lesion and intervention. Group (2): Injured animals with no treatment Group (3): Injured and injected with saline. Group (4): Injured and injected with HUCBs. Animals were subjected to behavioral assessment using two physiological tests. Histopathological sections and immunohistochemical examination were done. Results: The results of this study have shown that the HUCBs reduced the neurological function deficit to a moderate degree. Conclusion: Remyelination and new astrocyte formation could be established after HUCBs transplantation to the injured rats. (2012ESJ033)